Sound Absorption Performance Of Modified Concrete: A Review - Mo, Kim Hung; Ling, Tung Chai; Tie, Tzer Sheng; Alengaram, U.Johnson; Putra, Azma; Loo, Siaw Chuing (Elsevier Ltd, 2020)
Concrete, known as the second most consumed material in the world after water, is a versatile, inexpensive and durable construction material. Due to its high density, concrete is usually employed as rigid walls in buildings and also as sound barrier in highway. Researchers have proposed several methods to treat the concrete to also be capable of absorbing sound and thus improving the sound quality in a room. However, there exists limited information regarding the sound absorbing capability of concrete or more generally the cement-based materials. This paper reviews the sound absorption properties of various modified concrete materials from the existing published works. The influence of aggregate types and alteration of concrete ingredients on the acoustic properties of modified concrete materials are discussed. From the review, it is concluded that the sound absorption of the concrete or cement-based material can be improved by creating porous structures in the materials through different methods, namely incorporating lightweight aggregate, creating physical voids, such as in pervious concrete or by inducing voids with the inclusion of foam in cellular concrete. Another proposed method is also to incorporate large amount of hemp shiv to produce hemp concrete. A linear relationship is found to generally estimate the noise reduction coefficient as the function of the density of the materials using the data available from the published works.